Pengaruh Variasi Volume Serat Kawat Loket terhadap Sifat Mekanik Beton Mutu Normal - Adelia Ridha Sambesa; Nurul Hidayati; Aulia Muttaqin; Maya Saridewi Pascanawaty; Adryan Fitrayudha (Jurnal Talenta Sipil, 2026)
Concrete is a construction material that is widely used in infrastructure development due to its high compressive strength; however, it has relatively low tensile strength and exhibits brittle behavior. Various efforts have been made to improve the mechanical properties of concrete, one of which is through the addition of reinforcing materials such as PVC-coated welded wire mesh. Nevertheless, the effect of PVC-coated welded wire mesh on the mechanical properties of normal concrete still requires further investigation. This study aims to analyze the effect of adding PVC-coated welded wire mesh on the compressive strength and splitting tensile strength of normal concrete. The research method was conducted experimentally in a laboratory using cylindrical specimens measuring 15 cm × 30 cm, which were tested at the age of 28 days. The variations of welded wire mesh addition were 0% (normal concrete), 0.5%, 0.75%, and 1% of the concrete volume, with the same mix composition applied to all variations. Compressive strength testing was carried out in accordance with SNI 1974:2011, while splitting tensile strength testing followed the applicable standards. The results showed that normal concrete achieved the highest compressive strength of 25.32 MPa and splitting tensile strength of 13.76 MPa. The addition of PVC-coated welded wire mesh resulted in a decrease in compressive strength by 24.33% at 0.5%, 27.41% at 0.75%, and 71.00% at 1%, as well as a reduction in splitting tensile strength by 35.25%, 44.91%, and 38.37%, respectively. Based on these results, it can be concluded that the addition of PVC-coated welded wire mesh at the investigated variations was not able to improve the mechanical properties of normal concrete. Therefore, future studies are recommended to investigate variations in the shape, size, and configuration of the welded wire mesh, as well as the use of other admixtures to enhance workability and bonding performance in concrete